Heat on the street: exploring the role of heat and racial biases on traffic stops by police in California - Tan, Bin Qian (Nanyang Technological University, 2023)
Police officers typically work under physically demanding, time-sensitive and stressful conditions, while making discretionary decisions that potentially have substantial consequences. One possible arena whereby police officers exercise their own discretion on a daily basis is in traffic stops. Our study seeks to shed further light on racial profiling at traffic stops in the US, with a specific focus on the state of California. Previous studies have identified racial biases as a potential mechanism that leads to unobjective law enforcement by police officers, although the effect of heat on this mechanism has not been thoroughly explored. Using police stops data, weather data and sunset and sunrise timings in California within the time period of 2010 to 2018, we seek to replicate Grogger and Ridgeway’s Veil of Darkness test, before incorporating the effects of high temperatures into our analysis. We find that racial profiling of traffic stops exists in California, with a 1.4% decrease in traffic stops involving black drivers after dusk, compared to before sunset. However, we were unable to establish any causal mechanisms linking heat to the racial profiling of police stops. Our findings have implications for future police force reforms in California, as it is essential to address these racial biases to ensure that law enforcement is done on an objective, non-arbitrary basis.